Patient Relationship Management in Healthcare: Mapping the Knowledge Structure - Yunita Peggy Tappy; Deske W. Mandagi (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
Patient Relationship Management (PRM) has become increasingly important as healthcare systems move toward patient-centred, relationship-oriented, and digitally enabled models of care. However, PRM research remains fragmented across healthcare management, services marketing, nursing, organisational behaviour, medical informatics, and digital health, limiting understanding of the field’s intellectual development and thematic structure. This study addresses this gap by mapping the knowledge structure of PRM research in healthcare. A systematic literature review was combined with bibliometric performance analysis and science-mapping techniques to examine 147 peer-reviewed journal articles published between 1985 and 2025. The analysis identifies publication trends, methodological characteristics, theoretical foundations, influential journals, authors, institutions, countries, landmark publications, and major thematic clusters. The findings reveal four interconnected knowledge domains: healthcare quality and service management, nursing care and patient-provider relationships, human resources and organisational behaviour, and patient satisfaction and service evaluation. The temporal analysis further shows that PRM research has evolved through three phases, progressing from foundational quality management to relational consolidation and, more recently, digital and patient-centred expansion. Although survey-based quantitative research remains dominant, the growing use of artificial intelligence, machine learning, digital health systems, mixed methods, and intervention-based designs indicates increasing methodological and technological sophistication. The study contributes by consolidating fragmented research streams, clarifying the multidisciplinary foundations of PRM, and providing a structured overview of how organisational systems, professional capabilities, interpersonal interactions, and digital technologies jointly shape patient relationships. The findings establish a foundation for future research on PRM within increasingly complex and digitally mediated healthcare environments.